Kinetics and photophysical behavior of the P, N-ReI complex [P, N-{(C6H5)2(C5H4N)P}Re(CO)3(O-O3SCF3)]: A directly coordinated (and labile) triflate. (24th November 2017) - Prado, Gaspar; Ibañez, María Belén; Acosta, Alison; Chamorro, Eduardo; Hermosilla-Ibáñez, Patricio; Günther, Germán; Pizarro, Nancy; Vega, Andrés
Graphical abstract: The complex [ P, N -{(C6 H5 )2 (C5 H4 N)P}Re(CO)3 ( O -SO3 CF3 )] (RePNTfO ) experiences triflate exchange with coordinating solvents or bromide. Kinetic measurements lead to Δ H ≠, Δ S ≠ and Δ G ≠ equal to 50.8 kJ mol −1, −109.6 J K −1  mol −1 and 83.5 kJ mol −1 respectively, which are consistent with an intermediate associative ( I a ) mechanism for the exchange. Abstract: The reaction of [ P, N -{(C6 H5 )2 (C5 H4 N)P}Re(CO)3 Br] (RePNBr ) with silver triflate leads to the complex [ P, N -{(C6 H5 )2 (C5 H4 N)P}Re(CO)3 ( O -CF3 SO3 )] (RePNTfO ) with moderate yield. This new P, N -Re I triflate compound contains the anion directly coordinated to the metal, completing an octahedral environment.RePNTfO displays in dichloromethane (DCM) solution an irreversible oxidation about +1.35 V and three irreversible reduction processes at −1.38 V, −2.03 V and −2.30 V. Oxidation has been attributed to the Re I /Re II couple, while the reduction corresponds toPN -ligand processes, which is consistent with those computed by means of DFT. The absorption spectrum ofRePNTfO in DCM displays a maximum at 295 nm ( ε  = 7.1 × 10 3  M −1  cm −1 ) and a shoulder around 350 nm ( ε  = 1.8 × 10 3  M −1  cm −1 ), which have been assigned to intraligand (π → π ∗ ) and metal to ligand charge transfer (MLCT, dπ → π ∗ ) transitions with the help of DFT/TDDFT. Excitation ofRePNTfO in DCM at 350 nm leads to an emission spectrum centered at 535 nm. The analysis of the variation of the absorption and emission spectra in coordinating solvents compared to non-coordinating DCM, DFT/TDDFT calculations modeling and ELF analysis suggests for coordinating solvents that triflate ligand is replaced in the coordination sphere of Re I in solution. Kinetics of the exchange of triflate by bromide measured in DCM at different temperatures allowed to estimate the Eyring parameters: Δ H ≠, Δ S ≠ and Δ G ≠, 50.8 kJ mol −1, −109.6 J K −1  mol −1 and 83.5 kJ mol −1 respectively. The high negative entropy is indicative of a compact transition state, compatible with an associative mechanism, I a, for the exchange.